MERDEKA 74” (MINAPADI BERSAMA DENGAN IKAN LOKAL 7 SPESIES DAN 4 LEGOWO) - Mahendra Mahendra; Zuriat Zuriat; Alaudin Alaudin; Fazril Saputra; Sufal Diansyah; Citra Dina Febrina; Farah Diana; Muhammad Arif Nasution; Zulfadhli Zulfadhli; Fitria Rahmayanti (Jurnal Marine Kreatif, 2020)
The purpose of this Community Service is to apply the research results of the proposer team's research for community empowerment in Pante Ceureumen District, West Aceh. Research results are applied to the activity program MERDEKA 74 "(Minapadi Together with Local Fish 7 Species and 4 Legowo) which is a system of planting rice by cultivating fish in one rice field simultaneously. This program aims to increase farmers' income with high rice yield productivity and increase local fish production. The activity was carried out for 6 months at the Pante Ceureumen District, West Aceh. The results observed included rice production and fish production in the Minapadi system. The production of 2: 1 legowo planted rice has a significant effect on the parameters of rice production, namely (16.17 kg /Ha). Meanwhile, the production of cultivated fish (7 species) are catfish, bileh fish, tilapia, goldfish, catfish, catfish and giant prawns. The 7 species are able to develop and be cultivated well.